Air-Mobile Stroke Unit for access to stroke treatment in rural regions. Issue 6 (August 2018) - Walter, Silke; Zhao, Henry; Easton, Damien; Bil, Cees; Sauer, Jonas; Liu, Yang; Lesmeister, Martin; Grunwald, Iris Q; Donnan, Geoffrey A; Davis, Stephen M; Fassbender, Klaus
Background: In recent years, important progress has been made in effective stroke treatment, however, patients living in rural and remote areas have nil or very limited access to timely reperfusion therapies. Aims: Novel systems of care to overcome the detrimental treatment gap for stroke patients living in rural and remote regions need to be developed. Summary of review: A possible solution to the treatment disparity between stroke patients living in metropolitan and rural areas may involve the use of specially designed aircrafts equipped with the ability to diagnose and treat acute stroke at remote emergency sites. We describe technical solutions for an Air-Mobile Stroke Unit (Air-MSU) concept, where an aircraft is customized with the ability to perform multimodal computed tomography, in addition to onboard laboratory equipment and telemedicine connection. The Air-MSU is envisioned not only to allow intravenous thrombolysis in the field but also to allow prehospital triage to a comprehensive stroke center through use of contrast intracerebral vascular imaging. Several options for the Air-MSU approach are described, and issues regarding the potential medical benefit, optimal operating environment, technical realization, and integration in pre-existing solutions (e.g., flying doctor service) are addressed. Conclusion: The Air-MSU may represent a novel tool to reduce treatment disparity for stroke patients in rural and remote areas. However, this approach requires further implementation research to determine the overall benefit to these communities.